Purification of used Cooking Oil using a Combination of Activated Carbon and Bentonite Adsorbents - Aritonang, Barita; Ritonga, Ahmad Hafizullah; Harefa, Karnirius; Wiratma, Dicky Yuswardi; Herlina (Jurnal FARMASIMED (JFM), 2024)
The repeated use of cooking oil at high temperatures can significantly degrade its quality, as indicated by darkened color, unpleasant odor, elevated peroxide value (PV), and free fatty acid (FFA) levels. This deterioration can contribute to health risks such as obesity, high cholesterol, heart disease, and cancer. This study investigated the effectiveness of combined activated carbon and bentonite adsorbent in reducing peroxide value and free fatty acid levels in used cooking oil. The purification method involved an adsorption process using a combination of activated carbon derived from mangosteen peel waste and bentonite. The carbonization process was carried out at 600°C for 3 hours, followed by chemical activation with H?PO? at varying concentrations of 1M, 3M, and 5M. Bentonite was activated using 5M HCl. The results demonstrated that 5 grams of activated carbon from mangosteen peel, treated with 5M H?PO?, and bentonite activated with 5M HCl, were highly effective in lowering the peroxide value and free fatty acid levels in used cooking oil. Initially, the PV of the untreated used cooking oil was 16 meq O?/kg, reduced to 3.6 meq O?/kg after treatment with the combined adsorbents. Similarly, the FFA content decreased from 2.2% to 0.09%. Both peroxide value and free fatty acid levels met the standards set by SNI 3741:2013. In conclusion, using activated carbon and bentonite is an efficient method for purifying used cooking oil, as their strong adsorption capacity effectively reduces peroxide value and free fatty acid levels.